Specifics of population psychodiagnostics on the example of Kazakhstan, China, and Japan: a comparative analysis - Mynbayeva, Aigerim; Zhou, Mi; Minazheva, Gulsharat; Seiitnur, Zharas (Institute of Advanced Engineering and Science, 2025)
This research aimed at analyzing the history of psychological testing in three Asian countries (Kazakhstan, China, and Japan) in a comparative chronological aspect. A modern trend of interest in population psychodiagnostics was examined, considering a sample of university professors from the studied countries. The study had two stages: theoretical (cross-cultural analysis of the chronological development of psychodiagnostics in three countries) and experimental (in-depth interviews with professors). The study population was 72 respondents. As a result, two periods of psychodiagnostics were distinguished in each country: prescientific and scientific. The general factors influencing the historical development of psychological testing were: i) country’s history and influence of wartime; ii) positive and negative influence of ideology (communist and capitalist) on the psychometrics’ development; iii) the history of psychology and testing in particular, its methodology and methods; iv) the emergence of regional trends in the cooperation and countries’ level of publicity. Consequently, based on the interview, the testing of career interests and individual career guidance significantly dominated in China (4.8) while in Japan it was testing of interpersonal relationships (4.9). The present study may be in demand in future research to develop specific questionnaires and methods for studying the population considering national and historical characteristics.